PENGARUH CONTENT MARKETING DAN BRAND IMAGE THEYUJI TERHADAP KEPUTUSAN PEMBELIAN - Toii, Indra Eka Wardana; Edwar, Rizka Cintya; Landjang, Xenia Irene Sandy; Mangopo, Yuni Riskita; Damanik, Lisa Gresti Sella (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study aims to determine the effect of content marketing and brand image on purchasing decisions at the Theyuji Scraft store in Sorong City. This study uses a quantitative method. with a sample of 130 people. The quantitative data used in the study uses a Likert scale and the analysis used in this study is multiple regression and then the data is processed using SPSS 20. The results of this study indicate that content marketing has a positive and significant effect on purchasing decisions and brand image has a positive and significant effect on purchasing decisions